Syntagmatic and paradigmatic development of cochlear implanted children in comparison with normally hearing peers up to age 7. Issue 9 (September 2015) - Faes, Jolien; Gillis, Joris; Gillis, Steven
Abstract Objective Grammatical development is shown to be delayed in CI children. However, the literature has focussed mainly on one aspect of grammatical development, either morphology or syntax, and on standard tests instead of spontaneous speech. The aim of the present study was to compare grammatical development in the spontaneous speech of Dutch-speaking children with cochlear implants and normally hearing peers. Both syntagmatic and paradigmatic development will be assessed and compared with each other. Method Nine children with cochlear implants were followed yearly between ages 2 and 7. There was a cross-sectional control group of 10 normally hearing peers at each age. Syntactic development is measured by means of Mean Length of Utterance (MLU), morphological development by means of Mean Size of Paradigm (MSP). This last measure is relatively new in child language research. Results MLU and MSP of children with cochlear implants lag behind that of their normally hearing peers up to age 4 and up to age 6 respectively. By age 5, CI children catch up on MSP and by age 7 they caught up on MLU. Conclusion Children with cochlear implants catch up with their normally hearing peers for both measures of syntax and morphology. However, it is shown that inflection is earlier age-appropriate than sentence length in CI children. Possible explanations for this difference in developmental pace are discussed.